Terminal peace - Hines, Jim C. (Hines, Jim C. Janitors of the post-apocalypse, 2023)
Now in paperback, the third and final book of the Janitors of the Post-Apocalypse follows a group of unlikely heroes trying to save the galaxy from a zombie plague.